Pola Komunikasi Dosen Dalam Meningkatkan Kualitas Interpersonal Pada Mahasiswa Jurusan Ilmu Pemerintahan Universitas Pancasakti Makassar - Syaharuddin Syaharuddin (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
Communication has a role in building an organizational climate, which has an impact on organizational culture, namely the values ​​and beliefs that are the central point of the organization. The goal of communication in the organizational process is none other than to form mutual understanding (Mutual Undestanding). In short, so that there is equality in terms of reference and experience. Lecturer communication refers to patterns and forms of communication that occur in the context of organizational networks. This research aims to determine the communication patterns of lecturers in improving the interpersonal quality of students majoring in government science at Pancasakti University, Makassar. Data collection techniques were carried out through observation, interviews and literature study. The analytical method used is qualitative analysis. The research results show that good communication between lecturers and students will certainly result in better quality students, one of which is marked by increased student academic achievement. On the other hand, poor communication between lecturers and students will actually have an impact on decreasing the student's academic achievement. The indicators for the effectiveness of interpersonal communication, namely openness, empathy, supportive attitude, positive attitude, have worked well.